Multimorbidity: How about Information Access and Family Support? - Sijid, Rahmawati; Mulyani, Sri; Yanti, Fitri; Pujirana, Andi Asni; Rahayu, Yayu Puji (Universitas Mandala Waluya, 2023)
Multimorbidity is a consequence of epidemiological and demographic transitions. Multimorbidity, the co-occurrence of two or more chronic conditions, has become a priority agenda for many health policymakers and healthcare providers. Based on an initial survey, elderly people in Besu village experienced cases of multimorbidity, not only suffering from hypertension but also other diseases, namely diabetes mellitus and cholesterol. This research aims to determine the relationship between access to information and family support on the incidence of multimorbidity. The population of this study was 44 elderly participants at the Morosi Community Health Center in Besu Village, Morosi District, Konawe Regency, Southeast Sulawesi. The sample was 44 elderly people because it used total sampling. Data analysis used the Chi-square test. The research results show that access to information obtained a value of p = 0.000 and family support obtained a value of p = 0.047. In conclusion, a relationship exists between access to information and family support on the incidence of multimorbidity. So it is recommended that the community health centre provide easy access to health information for the community in the work area of ​​the community health centre about the importance of disease prevention through application media such as the one the author created, namely the M.Stepscoma application which is a medium for early stroke detection equipped with health education videos, apart from that the importance of family support through family assistance